Konflik Nilai-Praktik Konsumsi Halal: Analisis Perilaku Konsumen Muslim Perspektif Ekonomi Islam - Eka Putra, Yunanda; Sugianto; M Shabri Abd Majid (Forum Kerjasama Pendidikan Tinggi, 2025)
Halal product consumption behavior is a crucial issue in Islamic economic studies, especially amidst the rising religious consciousness among Muslims and the growth of the global halal industry. This research aims to systematically identify and map the factors influencing halal consumption behavior, the gap between religious values and actual consumption practices, and the challenges faced by Muslim consumers. This study is based on an in-depth analysis and synthesis of recent academic literature published between 2020 and 2025, sourced from various reputable scientific databases. The findings indicate that halal consumption behavior is influenced by religiosity, trust in certification labels, attitude, subjective norms, and halal literacy. Nevertheless, a gap was found between professed religious values and actual consumption decisions, particularly in non-food product categories. The main challenges include a lack of information, limited access to halal products, and the influence of modern lifestyles that obscure religious priorities. This study integrates Islamic positive and normative economic approaches to provide a comprehensive understanding of Muslim consumer behavior and offers recommendations for strengthening education and developing more contextual halal consumption policies.